ANALISIS KESALAHAN BERDASARKAN METODE NEWMAN MENGGUNAKAN CRI DIKAJI MENURUT GAYA BELAJAR SISWA DI SMAN - Octariana, Syariefah Fatimah; Yusmin, Edy; Astuti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research is aimed to recognize student?s error in completing quadratic inequalities questions based on the Newman method, besides that the researcher wants to discover student?s level of certainty using the Certainty of Response Index by examined the score that has been given and student?s learning style. The form of this research is a survey, therefore data presentation that has been done in the process of the research are the result of learning style questionnaire, quadratic inequalities essay test followed with CRI score by the students. The result from this research found that students with a predominantly visual learning style will conduct errors in transformation with low certainty level. Students with a predominantly auditory learning style will conduct errors in process skill and final result with high certainty level. Students with a predominantly kinesthetic learning style will conduct errors in process skill and final result with high certainty level.Keyword: Errors, Newman Method, Certainty of Response Index, Learning style